Enhanced ferroelectricity in PLZT ceramic by precise La-doping, minimizing pyrochlore phase and lead loss. (November 2018) - Samanta, Shibnath; Sankaranarayanan, V.; Sethupathi, K.; Ramachandra Rao, M.S.
Abstract: A comparative study correlating structure and ferroelectricity in La-doped PbZr0.52 Ti0.48 O3 [PZT] for La = 0–4% has been carried out. Due to increase in tetragonality, 2% La doped PZT shows highest polarization. A modified low cost, but highly proficient method of Double Atmospheric Layer Protected Sintering (DALPS) has been developed to sinter pyrochlore free 2% La-doped PbZr0.52 Ti0.48 O3 prepared by a modified sol-gel synthesis. The DALPS method enhances the remnant polarization by 29% and dielectric constant by 23% with around 50% decrease in dielectric loss tangent. The effectiveness of DALPS in preventing lead loss is confirmed by EDS analysis. As a result of the employment of the modified sol-gel synthesis and DALPS, a remnant polarization value as high as 49.25 μC cm −2 with nearly ideal hysteresis loop is observed in bulk Pb0.97 La0.02 Zr0.52 Ti0.48 O3 . The squareness factor of the P-E loop is 99.7% of an ideal value. The Positive Up Negative Down (PUND) measurement shows enhanced remnants with polarizations: the values of +dPr and –dPr are 112 and 117 μC cm −2 respectively. The dielectric loss is also sufficiently low and at room temperature and the value of tan δ is 0.016 with dielectric constant of 1369 at 1 kHz. Highlights: A modified synthesis route which produces pyrochlore free PLZT, is developed. Double Atmospheric Layer Protected Sintering is developed to reduce lead-loss. The observed remnant polarization is as high as 49.25 μC cm −2 . The squareness factor of P-E loop is 99.7% of an ideal value (2.00). The value of tan δ is 0.016 with εr ′ 1369 (for 1 kHz at 30 °C).